Role of biofertilizers in organic farming system - Kumawat, Kailash Chand (Indian Farming, 2022)
As a boon to farmers, the basic component of sustainable agriculture includes biofertilizers in the maintenance of longterm soil fertility, soil health and sustainability. For farmers to increase production per unit area in organic agriculture, biofertilization will be a viable choice for a period of prosperity and the clean climate. Excessive reliance on inorganic fertilizer is not a feasible strategy in the long term, both in the sense of cost and environmental effects of chemical fertilizer, because of the costs involved in the construction of fertilizer plant and the continuation of production in both domestic and foreign exchanges. Biofertilizers are products which, as soon as adequate information is given by producers and rural farmers, will be commercially promising in the long term. Biofertilizer utilization in country will not only have an effect on the economic development of sustainable agriculture but contribute to a sustainable environment and the overall wellbeing of India.